Gaya Hidup Komunitas Campervans di Bandung: Studi Kasus Komunikasi Lingkungan - Novianti, Felita Eka; Dirgantara, Pradipta (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Travel has evolved from mere tourism to mass tourism, focusing on leisure and recreational experiences. Nature-based tourism has become popular. Indonesia ranks 32 out of 117 in the Travel and Tourism Development Index, but limited accommodation options hinder its growth. The Ministry of Tourism plans to introduce campervans in 2022 to improve tourism quality. Therefore, research titled "Campervans Community Lifestyle in Bandung: A Case Study in Environmental Communication" is made, aiming to know the lifestyle of campervans community in Bandung as a case study in environmental communication. The research explores the campervan lifestyle in Bandung, a unique mode of transportation with various options for short-term and long-term travel. Despite its origins outside Indonesia, the lifestyle benefits society, and its adopters. However, the government in Bandung does not fully acknowledge or encourage it, leading to a demand for expedited permits and improved amenities